Mistisme Islam: Membincang Epistemologi Kaum Sufi - Zainuddin Puteh; M. Iqbal Irham; Sugeng Wanto (El-Afkar: Jurnal Pemikiran Keislaman dan Tafsir Hadis, 2022)
The spiritual emptiness of modern humans stems from the epistemology of Western positivism, which fails to fulfill its promise to bring humans to a happy standard of living. Therefore, it is necessary to study alternative epistemology for future knowledge for the sake of human happiness itself. As a mystical science in Islam, Sufism invites people to directly absorb knowledge from the "Source of Knowledge," Allah SWT. This kind of knowledge, of course, not only gives intellectual satisfaction but also heals the spiritual emptiness of today's man. This literature study concludes the research results through an analytical description. The study's results explain that Sufi epistemology emphasizes the subject (human) to obtain correct knowledge. Subjects who want to know must first purify their souls (qalb). After the soul is pure, then, like a mirror, the soul will catch and reflect that knowledge from Allah SWT because the proper knowledge in the study of Sufism is the light of Allah. To absorb light, the mirror must first be cleaned. That way, actual knowledge or nur will bring people happiness, not just intellectual satisfaction.